Scotland at the Russian Front in the First World War: Robert Scotland Liddell, War Correspondent and Photographer, Red Cross Worker and Russian Officer. (3rd July 2016) - Cross, Anthony
ABSTRACT: It is unlikely that one would encounter the name of Robert Scotland Liddell (1885–1972) in the list of eminent foreign correspondents covering the First World War in Russia for British newspapers and journals, but he deserves to be much better known both for the quality of the reports and photographs he sent from the Russian front for publication in the magazine The Sphere and for the trilogy of books that appeared in 1916–1917. Liddell began as an orderly attached to the Russian Red Cross in Poland in 1916 and after a period spent with Oliver Locker-Lampson's British Armed Car Division on the Romanian front, he became an officer in a Russian divisional transport unit and narrowly escaped execution by mutinous troops after the October coup before escaping from Russia at the end of 1917. The article, while concentrating on Liddell's reporting, experiences and exploits in Russia, attempts to survey his career from his early days as a Fleet Street journalist to the post-First World decades, when he wrote books of travel and novels, before sliding into obscurity.